PELATIHAN TERHADAP PRESTASI KERJA PEGAWAI PADA KANTOR GUBERNUR SULAWESI SELATAN (BIRO BINA PEREKONOMIAN) MAKASSAR - Vetty Vera; Hikmah Nurdin (UNIVERSITAS MUHAMMADIYAH MAKASSAR, 2019)
AbstractThe Office of the Governor of South Sulawesi (Biro Bina Perekonomian) Makassar has implemented training programs for research employees, such as types of training for research employees, including smart offices and MSMEs. But there is something that causes employees do not want to do the work, so there is disruption and decrease the performance of employees. The population of this study is employees of the Governor's Office of South Sulawesi (Bureau of Economic Development) Makassar which amounts to 38 employees with 33 civil servants and 5 non-civil servants. The analysis used to find out if there is a positive and significant influence of independent variables (X) on dependent variables (Y) is a simple regression. Based on spss output statistics 22.0 for windows, the simple linear regression equation can be formulated as follows: Y = 0.603 + 0.861X. The effect of training variables simultaneously positively affects employee performance is 55,055 with a significant value of 0.000. The effect of training variables has a positive effect on employee performance is 7,420 with a significant value of 0.000.